Effect of long-term Tillage and Nitrogen Fertilization Residue on Soil Biochemical Properties and Cowpea Yield - Rizki Afriliyanti; Sri Yusnaini; Agus Karyanto; Dwi Hapsoro; Ainin Niswati; Muhajir Utomo (JOURNAL OF TROPICAL SOILS, 2021)
Sustainable soil management practices must enhance or maintain soil quality and crop yields. The objective of this experiment was to study the effect of long-term (32 years) tillage system and nitrogen fertilization residue on soil biochemical properties and cowpea (Vigna unguiculata) yields. This research was conducted using four replications, a factorial experiment arranged in a randomized block design. The first factor was tillage systems consisting of intensive tillage (T1) and no-tillage (T2) and the second factor was nitrogen fertilization residue (N) consisting of N1 (0 kg N ha-1) and N2 (200 kg N ha-1). Data were analyzed using analysis of variance; if there was a significant difference will be continued with the Least Significant Difference (LSD) test at 5%. Principal Component Analysis (PCA) determined the relationship among observed variables. The results showed that no-tillage could give better results on soil respiration and soil bacteria and fungi population than intensive tillage. Lower soil pH was found at 200 kg N ha-1 fertilizer residue than control (without N fertilizer). The cowpea growth and yields were high at long-term N1T2 and N2T1 treatment. Principal component analysis showed an interrelationship among soil biochemical properties, growth, and yield of cowpea.